2019
DOI: 10.1177/1464884919854651
|View full text |Cite
|
Sign up to set email alerts
|

The seriousness of storytelling: What constraints to professional news routines reveal about the state of journalistic autonomy in local television newsrooms

Abstract: This study follows the advice of scholars James Carey and Barbie Zelizer in that it takes journalism seriously. The seriousness comes from the concern that modern corporate approaches to news production are contributing to the erosion of the professional status of journalists with restrictions to storytelling routines serving as one example of this issue. Using a multiple case study method, this research presents 180 hours of newsroom observations and interviews with 62 news professionals to identify some of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Like the newspaper business before them, television news ratings have plummeted (Barthell, 2018) as audiences scattered across digital platforms to include web, mobile, and social media news consumption habits. Many newsrooms across the country are now experimenting with ways to retrieve those lost television news audiences and to reach the younger, digital-native generations (Nesmith, 2016; Strohecker, 2018) by adopting digital production strategies and altering journalistic work routines (Henderson, 2019; Pavlik, 2000). The increasingly competitive marketplace has led to decreases in production of public affairs content (Yan and Napoli, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Like the newspaper business before them, television news ratings have plummeted (Barthell, 2018) as audiences scattered across digital platforms to include web, mobile, and social media news consumption habits. Many newsrooms across the country are now experimenting with ways to retrieve those lost television news audiences and to reach the younger, digital-native generations (Nesmith, 2016; Strohecker, 2018) by adopting digital production strategies and altering journalistic work routines (Henderson, 2019; Pavlik, 2000). The increasingly competitive marketplace has led to decreases in production of public affairs content (Yan and Napoli, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For journalists, along with changes to routines, scholars have observed, came changes to newsroom norms: To keep up with 24-hour news cycles and social media behaviors, verification gave way to immediacy (Hermida, 2015). To appear timelier and more omnipresent, newsrooms had storytelling take a back seat to live, breaking news presentations (Belt and Just, 2008; Henderson, 2019; Seib, 2001). And the long-reigning king of news norms, objectivity (Mindich, 2000; Schudson, 2001), moved aside for transparency (Hellmueller et al, 2013), possibly at the cost of credibility (Tandoc Jr. and Thomas, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…1). The emphasis of pushing journalists to diversify their production from a platform standpoint is potentially a result of trending data that shows a growing number of Americans receiving their news from online platforms (Henderson, 2019; Pew Research Center, 2018). According to the Pew Research Center (2018), approximately 50% of adults in the 18–29 and 30–49 categories obtain their news from online content producers.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Many stations will begin the morning meeting with discussions of potential weather threats. Managers will also encourage producers to lead with weather rather than news if enough of the viewership is affected, if the threat is significant even to a small section of the viewing area, or if the news lead is not strong enough (Henderson, 2015). By no coincidence, then, Pew research found that traffic, weather, and sports made up 40% of the morning and evening newscasts they analyzed (Jurkowitz et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, given the increased financial interest in a station’s digital products, some morning meetings now lead with which stories are trending online (Adornato, 2014; Henderson, 2015). As with weather, when a topic is given priority on the morning meeting’s agenda, it shapes coverage priorities either subtly or overtly.…”
Section: Literature Reviewmentioning
confidence: 99%